Data for: Foodborne hazards in food in Burkina Faso, 1990–2019: a systematic review and meta-analysis - Getachew, Dinede; Gazu, Lina; Alonso, Silvia; Mutua, Florence; Roesel, Kristina; Lindahl, Johanna; Amenu, Kebede; Sousa, Filipe; Ulrich, Pattama; Guadu, Tadesse; Dione, Michel; Ilboudo, Guy; et al. (2024)
Dataset contains information extracted from 14 articles: 12 were on bacterial hazards (Salmonella, Campylobacter, Staphylococcus, E. coli, Shigella), three on fungal hazards and one on parasitic hazards (Toxoplasma gondii). Dateset contains prevalence and microbial load of the hazards. Dataset could be used for estimating burden of disease related to the hazards and similar activities targeting the hazards.